2011
DOI: 10.4081/jear.2011.261
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of polyphenols-rich natural compounds as treatments to prevent attacks by subterranean and drywood termites: preliminary results

Abstract: -In the view to find sustainable methods to prevent termite attacks to wooden objects and structural timbers, this study represents a preliminary step in the evaluation of some natural substances considered as effective by some African popular traditions. Dark shea cake, obtained from the kernels of Vitellaria paradoxa (Sapotaceae), is the phase just before the extraction of shea (= karitè) butter. In some West African regions, by-products from this extraction are traditionally believed to protect houses from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
(9 reference statements)
0
4
0
Order By: Relevance
“…They found that the acqueous extract of these plants not only caused the mortality of tested termites, but also showed an important repellency to them. The repellent effect of extracts from few tropical plants on termite has also been reported by Maistrello et al (2011), Osipitan et al (2013) and Acda (2014).…”
Section: Introductionmentioning
confidence: 66%
“…They found that the acqueous extract of these plants not only caused the mortality of tested termites, but also showed an important repellency to them. The repellent effect of extracts from few tropical plants on termite has also been reported by Maistrello et al (2011), Osipitan et al (2013) and Acda (2014).…”
Section: Introductionmentioning
confidence: 66%
“…The plant is very common in the northern than southern parts of Ghana especially they are in abundance in Navrongo in the Upper East region of Ghana (Adelibigbe et al, 2017) [1] . It is a very common tree which occurs largely in off-reserves in some parts of Africa including northern Ghana (Maistrello et al, 2011;Jasaw et al, 2015) [14,12] . The plant is a nontimber forest product (NTFP) which means that it is a conserved biodiversity for enhancement of local livelihood and environmental sustainability (Jasaw et al, 2015) [12] .…”
Section: Introductionmentioning
confidence: 99%
“…Its kernels are used in production of shea butter which has gained popularity as a result of its application in food and cosmetic industries (Maistrello et al, 2011) [14] . The People employ the byproducts they obtain after extraction of sheabutter to prevent their houses from termites (Maistrello et al, 2011) [14] . The constituents of shea include saponins, alkaloids and polyphenols like tannins (Maranz et al, 2003; Ajijolakewu and Awarun, 2015) [15,2] .…”
Section: Introductionmentioning
confidence: 99%
“…Damage caused by subterranean termites, historically has been a concern of researchers worldwide [7]. Termites are among the worst pests for wooden structures and objects and their presence may also represent a serious threat for cultural heritage especially in those areas where climate and environmental conditions are especially favorable to these insects [8].…”
Section: Introductionmentioning
confidence: 99%